EFFECT OF ACTIVATION TEMPERATURE AND ZnCl2 CONCENTRATION FOR MERCURY ADSORPTION IN NATURAL GAS BY ACTIVATED COCONUT CARBONS - Lisna Rosmayati (Scientific Contributions Oil and Gas, 2015)
Elemental mercury from natural gas has increasingly become an environmental concern due to its high volatility and toxicity. Activated carbon adsorption is an effective mercury control method. Mercury content in natural gas should be removed to avoid equipment damage in the gas processing plant or the pipeline transmission system. This research describes the process of mercury removal from natural gas by coconut active carbon impregnated with ZnCl2. Activation temperature and ZnCl2 solution concentration are significant affect the mercury adsorption capacity. Charcoal was prepared from coconut shell and activated at 500, 700 and 900oC in constant fl ow of nitrogen. The effect of activation temperature and ZnCl2 concentration for mercury adsorption on adsorbent show that the adsorption ability of adsorbent is affected by increasing activation temperature up to an optimum temperature of 700oC. Ability of adsorption increases with increasing ZnCl2 concentration and mercury adsorption was optimum at 7% concentration of ZnCl2. The results indicated that the adsorption capacity of mercury in natural gas by activated carbon-impregnated chlor is very signifi cant. The conclusion of this paper is that optimum activation temperature 700oC and 7% ZnCl2 impregnated on adsorbent can improve the mercury adsorption in natural gas.